Slaying Excel dragons : a beginners guide to conquering Excel's frustrations and making Excel fun - Girvin, Mike (Holy Macro! Books, 2011)
"Provides information on efficiently creating Excel reports, covering such topics as keyboard shortcuts, style formation, formulas and functions, data analysis, charts, and conditional formatting."
Obsahuje rejstřík
Keywords: Microsoft Excel (software); tabulkové procesory; Microsoft Excel; electronic spreadsheets; příručky; handbooks and manuals